2021
DOI: 10.1039/d1tb01310f
|View full text |Cite
|
Sign up to set email alerts
|

Near infrared photothermal conversion materials: mechanism, preparation, and photothermal cancer therapy applications

Abstract: Photothermal therapy (PTT) has been widely applied in cancer therapy as a result of its non-invasive, localized treatment and good therapeutic effect. In general, the final therapeutic effect of PTT...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
134
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(152 citation statements)
references
References 153 publications
0
134
0
Order By: Relevance
“…Indeed, it has been reported that cancer cells have poor endurance to heat [ 252 ]. The photothermal effect of organic materials is associated with the transition of electrons in molecules when they are irradiated with light subjected to absorption, scattering, and transmission [ 253 ]. Additionally, carbon and inorganic materials, such as metals and metal oxide-based NPs, also offer advantageous photothermal features, as they present high photothermal efficiencies and intrinsic optical properties, such as the localized surface plasmon resonance (LSPR), among others.…”
Section: Light-responsive Polymersomes For Anticancer Therapeutic Del...mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it has been reported that cancer cells have poor endurance to heat [ 252 ]. The photothermal effect of organic materials is associated with the transition of electrons in molecules when they are irradiated with light subjected to absorption, scattering, and transmission [ 253 ]. Additionally, carbon and inorganic materials, such as metals and metal oxide-based NPs, also offer advantageous photothermal features, as they present high photothermal efficiencies and intrinsic optical properties, such as the localized surface plasmon resonance (LSPR), among others.…”
Section: Light-responsive Polymersomes For Anticancer Therapeutic Del...mentioning
confidence: 99%
“…In the case of PTT, they transform it into heat, increasing the temperature of the milieu, which is also called hyperthermia. In clinical settings, hyperthermia refers to treating diseases, such as cancer, through heating, inducing arduous processes, such as lysis of cell membranes, denaturation of proteins, or even evaporation of cytosol, leading to induced cell death [ 252 , 253 , 254 , 255 , 256 ]. Examples of polymersomes used in PTT are summarized in Table 3 .…”
Section: Light-responsive Polymersomes For Anticancer Therapeutic Del...mentioning
confidence: 99%
“…Interestingly, some tumor tissues faded away at the end of treatment with Ti 3 C 2 -Gel and NIR radiation. During the treatment, the temperature of the tumor tissues increased to 50°C within 2 min, which can disrupt the cell membranes of cancer cells; the underlying mechanisms resulting from PTT have been reported as follows: 1) inhibition of DNA, RNA, and protein synthesis at high temperatures; 2) changes in cell membrane permeability; 3) induction of immunogenic death of cancer cells due to the release of tumor-specific antigens; and 4) production of blood vessel spasms that result in intravascular thrombosis of tumor tissue ( Liu et al, 2019b ; Poursalehi et al, 2019 ; Ye et al, 2019 ; Shang et al, 2020 ; Chang et al, 2021 ; Li et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Photothermal conversion efficiency is defined as converting absorbed light energy into localized heat and usually mentioned as a percentage ( Table 2 ) [ 93 ]. Plasmonic NPs possess a wide conversion efficiency range in the NIR-I and NIR-II regions [ 83 , 92 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 ].…”
Section: Introductionmentioning
confidence: 99%